Pengaruh Promosi Konsumen Dan Media Sosial Instagram Terhadap Omset Penjualan: (Studi Kedai Sikok Lampung) - Sari, Widi Yana; Rahayu, Sri Ratnaning (Universitas Muhammadiyah Metro, 2021)
Yana Sari, Widi. 2021. The influence of Consumer Promotion and Instagram Social Media On sales Total in Sikok Lampung Eatery. Management Study Program, Economicis and Businees Faculty, Muhammadiyah University of Metro. Advisor (I) Ery Baskoro, S.E.,M.M. Advisor (II) Sri Retnaning Rahayu, S.E.,M.M. This study aimed to determine the effect of cosumer promotion, instagram media on sales total (omzet) of sikok lampung eatery. This reseach was conducted on consumers of sikok lampung eatery in 2021. By distributing questionnarires in the from of questions about consumer promotion and social media instagram. Then processed using SPSS 23 with the classical assumption test approach with the methods of normality, linearity, homogeneity. This research used quantitative methods with multiple linear regression analysis tools, T test, F test, determination to determine the effect of consumer promotion and social media instagram on the sales total of sikok lampung eatery. The results showed that simultaneously consumer promotion and social media instagram on sales turnover. Research partially showed that consumer promotion had a positive and insignificant effect on sales total. Keywords: Consumer Promotion, Instagram Social Media, Sales Total